Specchio-COVID19: a digital cohort study to improve public involvement in epidemiological research: Helene Baysson. (25th October 2022) - Baysson, H; Pennacchhio, F; Bal, A; Pullen, N; Lamour, J; Semaani, C; Zaballa, ME; Graindorge, C; Guessous, I; Stringhini, S
Abstract: Background: To manage the sanitary crisis and rapidly assess the seroprevalence of anti-SARS-CoV-2 antibodies in the canton of Geneva, we invited previous participants of an annual health survey of the general population to a first serological test. As the pandemic progressed, it become clear that there would be a significant longer impact on health and wellbeing of population. Moreover, there was a need to assess the adherence of the population regarding COVID-19 prevention measures, over time, as well as to provide scientific knowledge about antibodies dynamics and protection from new infections. For all these reasons, a long-term follow-up has been settled via the dedicated digital platform Specchio-COVID19 and on-line questionnaires and repeated serological tests. Methods: Several measures were designed to maintain high retention and involvement, including regular electronic newsletters with links to a "News" webpage, a "Research" webpage for dissemination of publications and the organization of webinars specifically dedicated to participants. A specific email address and a dedicated hotline were set up so that participants can get in touch with the Specchio-COVID19 team. Results: Specchio-COVID19 was launched in November, 2020. Up to February 2022, 10'946 individuals (57% women, median age 48) joined the project. Over time, participation rate remains around 65% for each release of questionnaire. 550 participants (5%) definitely dropped out. Conclusions: Our digital cohort facilitates participants' involvement, allowing participation from remote locations, organizing webinar, promoting news and scientific information via newsletters and specific webpages and enabling interaction between researchers and participants. Key messages: When designing the Specchio-COVID19 digital cohort, the purpose was not only to collect data. But to establish a reciprocal exchange of information between researchers and participants, fostering long-term involvement and health empowerment.